Rhinocerebral mucormycosis in a 5-month heart transplant recipient - Pedemonte-Sarrias, Gabriel (J Oral Maxillofac Pathol, 2015)
Mucormycosis is an opportunistic acute fungal infection with a high mortality rate seen in immunocompromised patients. It is extremely rare in heart transplant recipients. Rhinocerebral mucormycosis (RM) is the most frequently observed presentation. We report a case of RM in a heart transplant recipient 5-month after the procedure, with a fatal outcome.